From Scroll to Book: Maximizing Instagram by Nano-Micro Influencers Bookstagram to Increase Reading Interest in Indonesia - Nabilla Anasty Fahzaria; Izni Nur Indrawati Maulani; Aldin Aldama (Jurnal Komunikasi, 2025)
The rapid use of Instagram and the emergence of nano-micro influencers and the Bookstagram community are the background to this research, also focusing on the low interest in reading in Indonesia. In realizing reading behavior, their role in virtual space becomes urgent in providing information literacy. This study aims to explore the experiences of nano-micro Bookstagram influencers in maximizing the use of Instagram to increase interest in reading. This study will discuss how the phenomenon of reading interest in Indonesia is interpreted, the characteristics of their followers, and the strategies and techniques used to attract attention and increase audience engagement. The method used is qualitative research with a cyberphenomenology approach, where data was collected through in-depth interviews with 16 Indonesian nano-micro Bookstagram influencers, and data analysis followed Moustakas' 10 techniques. The results of the study provide an overview of internal and external factors that influence people's interest in reading, as well as typification of follower characteristics, such as learner followers, book recommendation collectors, and followers with positive attitudes. By utilizing Instagram features such as Reels, carousel post formats, Instagram Stories, Highlights, Shares, and Channels creatively, these influencers can increase interaction and expand their influence. The findings of this study also provide in-depth insights into the dynamics of communication in the digital era, especially in efforts to increase interest in reading in Indonesia. This research is expected to provide a significant contribution in understanding the role of influencers in advancing literacy in modern Indonesian society.